Enterprise application architecture with .NET Core : an architectural journey into Microsoft .NET open source platform /: an architectural journey into Microsoft .NET open source platform. (2017) - Senthilvel, Ganesan; Khan, Ovais Mehboob Ahmed; Qureshi, Habib Ahmed
No abstract available